High-grade myxofibrosarcoma of the maxillary sinus: A case report and literature review - Peter Yao; Theresa Scognamiglio; David Kutler (Otolaryngology Case Reports, 2021)
Background: We describe a rare case of high-grade myxofibrosarcoma (MFS) of the maxillary sinus and review the literature on MFS of the paranasal sinuses. Methods: A 66-year-old man presented for evaluation of 6–8 weeks of epistaxis and persistent nasal congestion and drainage. Imaging revealed a soft tissue mass extending from the left maxillary sinus into the left nasal cavity. After incomplete resection, the patient elected for post-operative radiotherapy, which was interrupted by rapid local progression. At this point, the patient underwent a total maxillectomy and adjuvant radiotherapy. Results: The patient was without evidence of recurrence at a follow-up visit 8 months after diagnosis. Conclusions: The recommended treatment of MFS is complete surgical resection. Margin status is the most important predictor of local recurrence. Our case, in which incomplete resection was followed by rapid local progression despite adjuvant radiotherapy, illustrates the unique challenges of treating MFS in the head and neck.